An Undergraduate Science Information Literacy Tutorial in a Web 2.0 World. - Jeanine Marie Scaramozzino (Issues in Science and Technology Librarianship)
The development of an interactive web-based science information literacy tutorial that introduces undergraduate science majors to basic components of scientific literature is described. The tutorial introduces concepts, vocabulary and resources necessary for understanding and accessing information. The tutorial content is based on the Association of College and Research Libraries (ACRL) Information Literacy Competency Standards for Higher Education and the Information Literacy Standards for Science and Engineering/Technology (American Library Association (ALA) /Association of College and Research Libraries (ACRL)/Science and Technology Section (STS) Task Force on Information Literacy for Science and Technology). In order to engage students in a Web 2.0 world, the tutorial has evolved to incorporate interactivity, graphics, and self-assessment. This paper provides information on the development of the tutorial, examples from the tutorial, suggestions for future designers, and the next steps in development of the tutorial and web-based tutorials. This tutorial fills a gap in information literacy as professors are trying to provide more instruction in limited classroom time and provides a resource that can be assigned or reviewed throughout a user's college career, reinforcing information literacy principles. This is especially important for science majors who, unlike social science and humanities majors, may not need to use science reference materials actively until upper division classes [ABSTRACT FROM AUTHOR]